Fly posting prohibition signage as a problem solving medium / Neesa Ameera Mohamed Salim ... [et al.] - Mohamed Salim, Neesa Ameera; Zainal Abidin, Shahriman; Mohd Khalis, Faryna (2012)
Fly postings are illegal advertisements on public properties. It is recognized as a national problem and becoming increasingly mainstreamed into conventional advertising. Failing to deal with the problem has an adverse effect on local communities , through the perception of crime and deterioration of the entire neighbourhood. Illegal advertisers do not feel guilty by defacing most of the public properties with fly postings . These advertisers are using this means of communication in the wrong direction as this advertising medium is strictly prohibited. Communication is fundamental yet it is too often taken for granted.